2015
DOI: 10.1016/j.joca.2015.02.949
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of symptomatic knee osteoarthritis in China: Results from China Health and Retirement Longitudinal Study

Abstract: Purpose: Vigorous physical activity is often considered a risk factor for knee and hip osteoarthritis (OA), but its effect on spinal OA is poorly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
120
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 0 publications
4
120
0
Order By: Relevance
“…For the people over 60 years old, the incidence of OA reaches as high as 42.8%. 3 In the early stages, the treatment of OA focuses on pain relief and symptom control. 4,5 In the advanced stage, there will be activity disorders and even disability, and joint replacement surgery will be the only therapeutic option.…”
Section: Introductionmentioning
confidence: 99%
“…For the people over 60 years old, the incidence of OA reaches as high as 42.8%. 3 In the early stages, the treatment of OA focuses on pain relief and symptom control. 4,5 In the advanced stage, there will be activity disorders and even disability, and joint replacement surgery will be the only therapeutic option.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that about 120 million people in China are suffering from OA and more than half of them are over 60 years old. Besides, the incidence of OA in female is higher than that in male [2]. OA is a kind of aseptic inflammatory disease, and its pathogenesis is considered as a specific immune response.…”
Section: Introductionmentioning
confidence: 99%
“…2 The incidence rate of OA is highest in the knee (knee osteoarthritis, KOA). 3 The elderly and women have a greater risk of developing OA. 4 With an increase in the aging population in China, KOA has become the most common and important joint disease and also one of the major causes of disability.…”
Section: Introductionmentioning
confidence: 99%
“…4 With an increase in the aging population in China, KOA has become the most common and important joint disease and also one of the major causes of disability. 3,[5][6][7][8][9] The disability rate is as high as 53%. According to the Global Burden of Disease 2010 study, 10 hip and knee OA was ranked as the 11th highest contributor to disability, with a worldwide KOA prevalence of 3.8%.…”
Section: Introductionmentioning
confidence: 99%